2014
DOI: 10.1001/jamainternmed.2014.3384
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Performance for Pharmacologic Venous Thromboembolism Prophylaxis and Rate of Venous Thromboembolism

Abstract: IMPORTANCE Hospitalization for acute medical illness is associated with increased risk of venous thromboembolism (VTE). Although efforts designed to increase use of pharmacologic VTE prophylaxis are intended to reduce hospital-associated VTE, whether higher rates of prophylaxis reduce VTE in medical patients is unknown.OBJECTIVE To examine the association between pharmacologic VTE prophylaxis rates and hospital-associated VTE.DESIGN, SETTING, AND PARTICIPANTS Retrospective, multicenter cohort study conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
97
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 30 publications
1
97
0
4
Order By: Relevance
“…The setting and design of HMS have been previously described. 12,13 Although voluntary, each hospital receives payments from Blue Cross Blue Shield of Michigan and Blue Care Network for participating in the consortium and for data collection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The setting and design of HMS have been previously described. 12,13 Although voluntary, each hospital receives payments from Blue Cross Blue Shield of Michigan and Blue Care Network for participating in the consortium and for data collection.…”
Section: Methodsmentioning
confidence: 99%
“…12 Using data from this collaborative, we conducted a retrospective study to assess the utility of the Caprini RAM in predicting risk of VTE in hospitalized medical patients.…”
Section: Introductionmentioning
confidence: 99%
“…2–3 Recent evidence suggests that higher rates of VTE prophylaxis in the absence of formal VTE risk stratification may not lead to reduced VTE rates. 4 …”
Section: Introductionmentioning
confidence: 99%
“…13 Research by hospitalists in this area has shown that rates of pharmacologic prophylaxis are low in US hospitals. 14 The Joint Commission and the CMS has a performance measure for VTE prophylaxis aimed at increasing the rate of prophylaxis in hospitalized patients. The Society of Hospital Medicine (SHM) has supported hospitalists in their endeavors toward system-based initiatives to improve quality of care.…”
Section: Venous Thromboembolism Prophylaxismentioning
confidence: 99%